Perinatal Morbidity Among Mothers of Medically Fragile Infants [3N]. (May 2017) - Stuebe, Alison; Tucker, Christine; Ferrari, Renee; Funk, Michele Jonsson; Bryant, Katherine; Verbiest, Sarah
Abstract : INTRODUCTION: Mothers of medically fragile infants (MMFI) must recover from birth while attending to an infant in the neonatal intensive care unit (NICU). We hypothesized that, compared with mothers of well babies (MWB), MMFI would have more chronic medical problems and obstetric complications, increasing their need for postpartum follow-up. METHODS: Retrospective cohort study of mothers delivering at North Carolina Women's Hospital between 7/1/2014 and 6/30/2015. We defined MMFI as mothers of infants with a NICU length of stay of 3 or more days and MWB as mothers of infants not admitted to NICU. Outcomes were ascertained from the UNC Perinatal Database. We used chi square tests to compare health status and perinatal complications among MMFI, mothers of infants with NICU stays less than 3 days, and MWB. P values less than .05 were considered statistically significant. RESULTS: Among the 3, 502 women who delivered a live-born infant, 10.5% were MMFI, 4.9% had an infant with a NICU stay less than 3 days, and 84.6% were MWB. MMFI were more likely than MWB to deliver by c-section (53.3 vs 24.4%, P < .01), be transfused with packed Red Blood Cells (5.7 vs 2.2%, P < .01) or Fresh Frozen Plasma (1.4 vs 0.37%, P=.04), and have chronic hypertension (16.0 vs 5.1%, P < .001), severe preeclampsia (24.7 vs 2.6%, P < .01) or HELLP syndrome (4.4 vs 0.3%, P < .01). CONCLUSION: MMFI have a greater burden of chronic disease and perinatal morbidity than MWB. Targeted approaches are needed to support the wellbeing of MMFI.